Patient‐centred value framework for haemophilia. Issue 6 (6th April 2018) - O'Mahony, B.; Dolan, G.; Nugent, D.; Goodman, C.; ,
Abstract : Introduction: Growing budgetary demands have led to increased scrutiny of healthcare spending for rare diseases, leading to a unified goal within the haemophilia community to define objectively patient‐centred value in haemophilia care. Aim: To develop a patient‐centred outcomes framework with global applicability for assessing value in haemophilia healthcare. Methods: An international, multidisciplinary panel of experts convened to identify the range of patient impacts of haemophilia health care and organize these into a three‐tiered, patient‐centred outcomes framework based on Porter's model for assessing value. Results: In addition to measures common to other chronic diseases (eg survival and quality of life), Tier 1, health status achieved or retained, includes haemophilia‐specific outcomes of bleeding frequency, musculoskeletal complications and life‐threatening bleeds, as well as measures of function or activity. Tier 2, process of recovery, includes such outcomes as time to initial treatment, time to recovery and time missed at education/work; also included are disutility of care, measured by inhibitor development, pathogen transmission/infections, orthopaedic intervention and difficult venous access. Tier 3, sustainability of health, is measured by bleed avoidance, maintenance of productive lives and good health over time; potential long‐term negative consequences include insufficient or inappropriate therapy and age‐related complications. The applicability of the outcomes framework for different types of haemophilia healthcare interventions is described. Conclusion: Haemophilia health care can affect multiple patient‐centred outcomes across diverse patient types and healthcare systems. This framework organizes those outcomes for informing value‐based decision making by multiple stakeholders and provides the basis for further refinement and development of a standardized outcomes set.